Substitution and expansion effects in Greek agriculture: analysis with a non-parametric approach - Παπακωνσταντίνου Ασπασία; Φουσέκης Παναγιώτης (SPOUDAI Journal of Economics and Business, 2001)
The substitution and expansion effects in Greek Agriculture, for the period 1970-93 are analyzed with a recently developed non-parametric approach. The results indicate that the intermediate inputs are substitutes for land and labor and complements to capital. Labor is substitute for capital, land is complement to labor and substitute for capital. The substitution effects outweigh the expansion effects for all inputs but land. The expansion effects work towards raising the use of labor and land at the expense of capital and intermediate inputs. JEL Classification: C14, C15, D24